Enrôlement sanitaire et subjectivation de la maternité en milieu populaire dans le Nordeste brésilien : le « rôle maternel incarné » - Alfonsina Faya Robles (Enfances, Familles, Générations, 2018)
The massive development of the Brazilian public health system over the past two decades has given rise to new practices and new forms of participation amongst working-class women. As a consequence, maternal care in North-East Brazil is being developed more and more through public health programs. Women are being called upon to act as agents for change and to play a health management role as concerns their children. Under the terms of these health programs, the bodies of poor women are targeted by regulations that seek positive health results. This widening of the public health compass has led not only to new physical constraints, and new forms of legitimization of medical intervention, it has also created room for the development of new areas of maternal subjectivity.